Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s10456-021-09809-2
|View full text |Cite
|
Sign up to set email alerts
|

CCM2-deficient endothelial cells undergo a ROCK-dependent reprogramming into senescence-associated secretory phenotype

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 78 publications
4
20
0
Order By: Relevance
“…1 b) were both upregulated. These findings were also confirmed by transcriptomic data from siCCM2 -treated HUVECs 35 . Interestingly, another common finding in all three CCM models was the simultaneous upregulation of genes encoding RA degrading enzymes Cyp26A or Cyp26B (Fig.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…1 b) were both upregulated. These findings were also confirmed by transcriptomic data from siCCM2 -treated HUVECs 35 . Interestingly, another common finding in all three CCM models was the simultaneous upregulation of genes encoding RA degrading enzymes Cyp26A or Cyp26B (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Based on the differentially expressed genes in mice, we data mined the published CCM2-knock-out zebrafish dataset, which was based on whole heart tissue 34 . The same was done for siCCM2 -treated HUVECs, for which transcriptomic data had recently been published 35 . Fold changes of genes of interest were visualized by grouped sizes of circles and plotted on a chart in an alphabetical order.…”
Section: Methodsmentioning
confidence: 99%
“…CCM3 mutations tend to appear earlier with a more severe pathobiology [ 254 ]. Interestingly, CCM mutations result in RhoA and RhoA kinase (ROCK) activation which impairs EC barrier function and promotes a senescence-associated secretory phenotype; statins and drugs that inhibit ROCK can reduce CCM lesions in mice [ 255 , 256 ]. Many CCM lesions present as hyperpermeable tangles of vessels that resemble transformed ECs in vascular-derived malignancies such as hemangiosarcoma.…”
Section: Angiogenesis and Anti-angiogenesis In Diseasesmentioning
confidence: 99%
“…Vannier et al reported the loss of CCM1 and CCM2 in endothelial cells (HUVECs) triggers them to transition to a senescence-associated secretory phenotype via activation of Rho-associated coiled-coil containing protein kinase 2 (ROCK2). The authors had also proposed that the SASP changes the tissue microenvironment by increasing extracellular matrix degradation (Vannier et al, 2021). Kiss and colleagues identified senescent cerebromicrovascular endothelial cells in the aged mouse brain using complex analyses of single-cell RNA sequencing data (Kiss et al, 2020).…”
Section: Endothelial Senescence In Diabetes and Metabolic Diseasesmentioning
confidence: 99%